(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The image of warrior women has persisted throughout global folklore and mythology as a symbol of strength, independence, and courage. From Amazons in Greek legends to Tomyris in Central Asian lore, mythical warrior women have been portrayed in various artistic forms as complex characters that challenge traditional gender roles. This article explores the artistic depiction of such mythical female warriors in world folklore, literature, and visual arts, highlighting their symbolic meaning and transformation over time.